(untitled) (Bangladesh Journal of Medicine, 2023)
Tietze syndrome is a benign inflammation of one or more of the costal cartilages. The condition is characterized by tenderness and painful swelling of the anterior (front) chest wall at the costochondral (rib to cartilage), sternocostal (cartilage to sternum), or sternoclavicular (clavicle to sternum) junctions. We describe a previously healthy 35 years old gentleman with repeated presentations to the emergency department (ED) with left-sided chest and sternoclavicular pain on a background of recent asymptomatic COVID-19 infection. Labs and imaging subsequently confirmed the diagnosis of Tietze’s syndrome. Anti-inflammatory medications and colchicine eventually led to uneventful recovery. This case highlights how Tietze’s syndrome — a disorder that is potentially self-limiting, can cause recurrent hospital admission and should be a differential diagnosis of chest pain related to COVID-19. Bangladesh J Medicine 2023; 34(2): 155-159